EDUKASI LITERASI FINANSIAL KEPADA SISWA KELAS 9 MTS NURUL HIKMAH GANTAR EDUCATING FINANCIAL LITERACY TO 9TH GRADE STUDENT IN MTS NURUL HIKMAH GANTAR - Nissa Nurhadidah Faried; Cameila Alya Yahya; Wahyudin; Jidan Ahmad Pratama; Irvan Iswandi (Pusat Riset dan Inovasi Nasional, 2022)
Financial literacy is necessary be given since early childhood. The low quality of financial education in Indonesia is marked by the hyped consumptive and hedonist lifestyle, result in not prepared future saving, due to their willing to prefer current joy rather than to postpone for the greater. Financial literacy is given to the student to comprehend priority of necessity, avoiding consumptive and hedonist lifestyle, and for them to prepare the future saving. The aim of this activity is to increase the understanding of how to manage financial. This method of activity is started by planning, implementation, and ended by evaluation. This activity result in the increased understanding of financial literacy.